MASA KERJA, STATUS GIZI, IKLIM KERJA, BEBAN KERJA, POSTUR KERJA DENGAN KELELAHAN KERJA : KAJIAN PUSTAKA - Indah Simanjuntak; Yuliani Setyaningsih; Ida Wahyuni (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2020)
Background: Fatigue is a mechanism of protection that is owned by someone against psychosocial stress that they experience during a certain period of time. Work fatigue can be used as a marker if workers experience health problems while doing their work. Objectives: This study aims to analyze the relationship between tenure, nutritional status, work climate, physical workload, and work posture with work fatigue. Research Metodes: The method used in this study is a quantitative literature study. Literature data is obtained through online from several trusted websites or internet sites such as Sciendirect, JSTOR, Cambridge Core, Scopus, and Goggle Cendikia. Results: This research was conducted on 20 articles consisting of 15 national articles and 5 international articles. Articles are analyzed bivariately and processed through stages in the form of organizing, synthesizing, identifying, and formulating. In general, the 20 articles said that all workers experienced fatigue. Conclusion: Five out of ten articles stated that there was a significant relationship between tenure and discharge, the rest stated that they did not have a relationship. Then for nutritional status has varied results, three of the eight articles stated there was a relationship between nutritional status with work fatigue, the rest of the article stated no relationship. In addition, there is a significant relationship between work climate with work fatigue in all articles. Furthermore there is a significant relationship between physical workload with work fatigue. and the last work posture has a significant relationship with work fatigue, amounting to 4 articles.